Why Do Most Children Not Walk or Cycle to and from School? - Fitriani, Anna; Hidayati (Universitas Airlangga, 2025)
Background: Physical activity plays a crucial role in children's health and well-being. Active school commuting (ASC), one of the strategies to enhance physical activity among children, has declined globally. However, no data is available for Indonesian children. None of the determinants of children’s ASC has been examined in Indonesian studies. Objectives: This study aimed to 1) measure the ASC rate and 2) analyze the association between individual, social, and physical environmental factors, and the ASC rate among primary school children in three urban areas in Indonesia (South Jakarta, Central Jakarta, and South Tangerang). Methods: This is a cross-sectional study using an online survey completed by mothers as representatives of their children. The survey was completed by 441 parents from 9 primary schools in South Jakarta, Central Jakarta, and South Tangerang. Results: 1) Only 28.3% of children engage in ASC (walking or cycling), 2) individual factor (‘do not dare to go to school alone’), social factors (‘having a friend for going to school’ and ‘afraid of street crime’), and environmental factors (inadequacy of public transport, broken roads, and school distance) are significantly associated with ASC. Conclusion: less than one-third of primary school children in South Jakarta, Central Jakarta, and South Tangerang walk or bike to go to and back from school. Perceived individual, social, and environmental factors might hinder active school commuting among children. Future interventions need to attenuate negative perceptions toward ASC from individual, social, and environmental perspectives.